STUDENTS PERCEPTION ON THE TEACHER NONVERBAL COMMUNICATION AT THE SEVENTH GRADE STUDENTS OF MTSS NAGARI BINJAI - Riya Arima; Irwandi Irwandi; Reflinda Ali (ELTR Journal, 2021)
ABSTRACT The research was due to several problems found in the field: the teacher did not usually used nonverbal communication in English classroom. It is indicated by the English teacher when the researcher did the preliminary research when teaching learning process in this class. It is indicated when the teacher try to silent to make the students pay attention but the fact some of students still make noise and not pay attention to the teacher in this class. The result of the research: first students perception on teacher’s gesture with 34,09% in rating quality of good. Second, students perception on teacher’s facial expression with 36,4% in rating quality of good. Third, students perception on teacher’s eye contact with 27,7% in rating quality of moderate. Fourth, students perception on teacher’s pitch with 18,45% in rating quality of poor. Fifth, students perception on teacher’s rate with 36,9% in rating quality of good. Sixth, students perception on teacher’s pause with 36,4% in rating quality of good. Seventh, students perception on the teacher’s friendship and warmth with 31,85% in rating quality of good.